PENGEMBANGAN LABORATORIUM VIRTUAL BERBASIS TIKTOK PADA MATA KULIAH PRAKTIKUM KIMIA DASAR 1 UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN PROSES SAINS - Aisyiah Restutiningsih Putri Utami; Mustapa Mustapa; Chaleb Paul Manaari; Tika Putri Agustina; Musma Rukmana; Ermita Ermita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
The aim of this study was to develop a virtual laboratory TikTok-based. The virtual laboratory was designed for basic chemistry 1 labwork. The developed media was created to increase students' critical thinking and science process skills. The methodology of this research used ADDIE model. The virtual laboratory validations to evaluate the content and media were successfully done by two experts on each validation. Based on the validations, the score results were 93,6% for content and 88,1% for media. It means that the virtual laboratory was successfully created and is ready to be used as a teaching-learning source. The practical and effective tests were done in the chemistry education program grade 1 at A and B class. The data collection was through direct observation, interviews, and questionnaires. Next, the data was analyzed by descriptive statistic method. The research result showed that the Tiktok virtual laboratory was very good, practical, and effective to use in basic chemistry 1 labwork and could increase students' science process and critical thinking skills with an effectiveness percentage of 89,7%.